Distributed Plant Hydraulic and Hydrological Modeling to Understand the Susceptibility of Riparian Woodland Trees to Drought‐Induced Mortality. Issue 7 (21st July 2018) - Tai, Xiaonan; Mackay, D. Scott; Sperry, John S.; Brooks, Paul; Anderegg, William R. L.; Flanagan, Lawrence B.; Rood, Stewart B.; Hopkinson, Christopher
Abstract: The mechanistic understanding of drought‐induced forest mortality hinges on improved models that incorporate the interactions between plant physiological responses and the spatiotemporal dynamics of water availability. We present a new framework integrating a three‐dimensional groundwater model, Parallel Flow, with a physiologically sophisticated plant model, Terrestrial Regional Ecosystem Exchange Simulator. The integrated model, Parallel Flow‐Terrestrial Regional Ecosystem Exchange Simulator, was demonstrated to quantify the susceptibility of riparian cottonwoods ( Populus angustifolia, Populus deltoides, and native hybrids) in southwestern Canada to sustained atmospheric drought and variability in stream flow. The model reasonably captured the dynamics of soil moisture and evapotranspiration in both wet and dry years, including the resilience of cottonwoods despite their high vulnerability to xylem cavitation. Unrealistic predictions of mortality could be generated when ignoring lateral groundwater flow. Our results also illustrated a mechanistic linkage between streamflow and cottonwood health. In the absence of precipitation, normal streamflow could sustain 94% of cottonwoods, and higher streamflows would be required to sustain all of the floodplain cottonwoods. Further, the risk of mortality was mediated by plant hydraulic properties. These results underpin the importance of integrating groundwater processes and plant hydraulics in order to analyze the forest response to sustained severe drought, which could increase in the future due to climate change combined with increasing river water withdrawals. Key Points: Plant hydraulics and hydrology are integrated Role of alternate water sources in sustaining cottonwoods is assessed Susceptibility to different streamflows is predicted